2012
DOI: 10.3109/s10165-011-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of neuro-Behcet’s disease in Japan: a multicenter retrospective analysis

Abstract: To delineate the clinical characteristics of neuro-Behçet's disease (NBD), a multicenter retrospective survey was performed in BD patients who had presented any neurological manifestations between 1988 and 2008. The diagnosis of acute NBD, chronic progressive (CP) NBD, and non-NBD was confirmed by retrospective review of clinical records. Data on a total of 144 patients were collected; 76 with acute NBD, 35 with CP NBD, and 33 with non-NBD. High-intensity lesions on T2-weighted magnetic resonance imaging (MRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…Although no consensus definition for NBD exists, the diagnosis is generally made in a BD patient with headache or neurological symptoms in the presence of compatible abnormalities on neuroimaging. 2,6,7 Approximately 5-15 % of those with BD subsequently develop NBD, 6,8 but 45 % of those with NBD will have moderate to severe neurological disability at 10-year follow-up. 2 It remains unclear if the prompt recognition and specific treatment of NBD would improve long-term prognosis, 6,8 but the diagnostic approach to headache and use of neuroimaging in BD can be categorized by the types of headaches experienced by BD patients and associated clinical features (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although no consensus definition for NBD exists, the diagnosis is generally made in a BD patient with headache or neurological symptoms in the presence of compatible abnormalities on neuroimaging. 2,6,7 Approximately 5-15 % of those with BD subsequently develop NBD, 6,8 but 45 % of those with NBD will have moderate to severe neurological disability at 10-year follow-up. 2 It remains unclear if the prompt recognition and specific treatment of NBD would improve long-term prognosis, 6,8 but the diagnostic approach to headache and use of neuroimaging in BD can be categorized by the types of headaches experienced by BD patients and associated clinical features (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8 In contrast, venous sinus thrombosis is the most common presentation of the second form of NBD, which is considered non-parenchymal or vascular NBD. 2,[6][7][8][9] Nearly all present with headache and papilledema, and less commonly with pyramidal signs. 8 Therefore, headache in the absence of other signs and symptoms would be an unusual presentation for NBD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2,9,[11][12][13][14][15][16][17]20,30,[34][35][36][37][38][39][40] Moreover, warfarin and acetyl salicylic acid have been given to some CVT patients with BD. [10][11][12]17,26,34 Wechsler et al 14 reported that treatment of CVT during acute phase consisted of combined heparin and steroids in 19 patients, steroids alone in three, and heparin alone in three others.…”
Section: Resultsmentioning
confidence: 99%